2019
DOI: 10.2147/ndt.s205014
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between <em>ADORA2A</em> gene polymorphisms and schizophrenia in the North Chinese Han population</p>

Abstract: BackgroundA large number of studies have shown a close relationship between ADORA2A and the pathological mechanism of schizophrenia. However, to our knowledge, there has been no studies examining the association between the ADORA2A gene and schizophrenia in Chinese Han population.PurposeThe objective of this study was to examine the relationship between adenosine A2A receptor (ADORA2A) single nucleotide polymorphisms and schizophrenia in the North Chinese Han population.Patients and methodsWe detected ADORA2A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In accordance with such hypotheses, A 2A R were found to be upregulated in the striatum [ 183 , 184 ] and hippocampus [ 185 ] of chronic schizophrenics (although this upregulation could also be a consequence of the antipsychotic treatment that the patients received). A Chinese study reported significant associations between single nucleotide polymorphisms of the A 2A R gene and schizophrenia in the northern Chinese Han population [ 186 ].…”
Section: A 2a R-d 2 R Interamentioning
confidence: 99%
“…In accordance with such hypotheses, A 2A R were found to be upregulated in the striatum [ 183 , 184 ] and hippocampus [ 185 ] of chronic schizophrenics (although this upregulation could also be a consequence of the antipsychotic treatment that the patients received). A Chinese study reported significant associations between single nucleotide polymorphisms of the A 2A R gene and schizophrenia in the northern Chinese Han population [ 186 ].…”
Section: A 2a R-d 2 R Interamentioning
confidence: 99%
“…However, the underlying mechanism mainly focused on purinergic receptor polymorphisms and interaction with dopamine receptors and NMDA receptors. The link between adenosine A2A receptor gene polymorphism located on chromosome 22q and susceptibility to SZ was reported [93,94]. By measuring the polymorphisms in ADORA1, ADORA2A, and ADORA3, a study found a correlation between ADORA1 rs3766566 and positive psychopathological symptoms, ADORA2A rs2298383 and general psychopathological symptoms, and ADORA2A rs5751876 and akathisia [95].…”
Section: Gpos In Neuropsychiatric Disordersmentioning
confidence: 99%
“…A2a receptor provides a candidate schizophrenia susceptibility gene [163], which, again, ties the adenosine A2a receptor to various mental disorders that include schizophrenia, as well as depression and anxiety. As indicated by a variety of studies, the adenosine A2a receptor "fine tunes" glutamatergic and dopaminergic network balance [164].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…This appears to be particularly likely in relation to A 2A receptor-D 2 receptor heteromers and potentially accounts for their known allosteric mechanisms and multiple unique pharmacological and biochemical properties. On chromosome 22q12–13, a single nucleotide polymorphism (SNP) on the A2a receptor provides a candidate schizophrenia susceptibility gene [ 163 ], which, again, ties the adenosine A2a receptor to various mental disorders that include schizophrenia, as well as depression and anxiety. As indicated by a variety of studies, the adenosine A2a receptor “fine tunes” glutamatergic and dopaminergic network balance [ 164 ].…”
Section: Gpcrs In Cnsmentioning
confidence: 99%